Interdisciplinary learning combining engravings and poems by teachers in initial training - Peña-Acuña, Beatriz; Assaleh Assaleh, Samir (Frontiers in Education, 2024)
Interdisciplinary is proposed to address a technologic knowledge-based society. This research employs quantitative methodology to analyze the perception of an integrated interdisciplinary practice involving engraving and poetry among 63 teachers in initial training. The goal is to identify correlations between age, gender, and the three dimensions of interdisciplinary. We infer a moderate positive correlation between age and the perception of skills, and a weak correlation with the perception of knowledge and interdisciplinary attitude dimensions, yielding results. This research aligns with the stance in favor of interdisciplinary education, advocating for its importance from pre-university to university levels, as a preparation for students to tackle complexity.